Myths and Facts About the Effects of Ischemic Preconditioning on Performance - Marocolo, M.; da Mota, G. R.; Simim, M. A. M.; Appell Coriolano, H.-J. (International Journal of Sports Medicine, 2016)
Although numerous studies have demonstrated the effect of ischemic preconditioning (IPC) in clinical application, the effectiveness of this procedure on performance and physiological variables is still debatable. Therefore a systematic review was performed, including a meta-analysis and evaluation of the quality of the papers that addressed this scope. The electronic databases of the National Library of Medicine (PubMed), Google Scholar (using [advanced search], [all fields]) and other online journals were searched, for the following descriptors: a) “ischemic preconditioning”; b) “blood flow” and “hyperemia”; c) “blood flow occlusion,” combined with “exercise performance”, “athletes”, “exercise” and “performance”. Relevant studies were included, if they conformed to strict pre-formulated criteria, excluding systematic review articles, meta-analyses and studies with only animals or non-healthy subjects. The 20 studies included had high quality scores (87%). The majority of the studies lacked statistical significance (P<0.05) for both performance and physiological variables when comparing IPC, placebo and control groups. Most studies showed that IPC has no significant influence on performance. The few studies with significant differences mainly described an improvement only in performance without altered physiological parameters. Therefore, the influence of IPC on performance is still unclear and physiologically highly debatable.
Keywords: blood flow occlusion; hyperemia; sports; testing